New journeys in Iberian studies : a (trans- )national and (trans- )regional exploration - Gant, Mark; Ruzzante, Paco; Hatton, Anneliese (Cambridge Scholars Publishing, 2018)
The research collected in this volume consists of 18 chapters which explore a number of key areas of investigation in contemporary Iberian studies. As the title suggests, there is a strong emphasis on trans-national and trans-regional approaches to the subject area, reflecting current discourse and scholarship, but the contributions are not limited by these approaches and include an eclectic range of recent work by scholars of history, politics, literature, the visual arts and cultural and social studies, often working in transdisciplinary ways. The geographical scope of the transnational proc.